2021
DOI: 10.3390/s21175932
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the CORE Sensor to Assess Core Body Temperature during Cycling Exercise

Abstract: Monitoring core body temperature (Tc) during training and competitions, especially in a hot environment, can help enhance an athlete’s performance, as well as lower the risk for heat stroke. Accordingly, a noninvasive sensor that allows reliable monitoring of Tc would be highly beneficial in this context. One such novel non-invasive sensor was recently introduced onto the market (CORE, greenTEG, Rümlang, Switzerland), but, to our knowledge, a validation study of this device has not yet been reported. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 25 publications
5
29
0
Order By: Relevance
“…In the case of manual labor work settings, where workers typically endure 8+ hour shifts and must stay safe in the heat, it is preferable to slightly overestimate T C (vs. underestimate) in order to protect these workers from heat-related injuries and illnesses throughout the day. As such, Kenzen’s T C algorithm was designed to slightly overestimate (vs. underestimate) T C at these dangerous T C ranges in order to protect workers, whereas previous algorithms or wearable devices have been shown to underestimate T C at these higher temperatures [ 20 ], which can put workers at even greater risk for heat injury and illness if solely relying on the wearable device for safety feedback. Another point to note is that this slight overestimation of core temperature at T C ≥ 38.5 °C may be even greater when compared to the gold-standard T C measurement of esophageal temperature, since gastrointestinal and rectal temperatures tend to be ~0.24–0.28 °C higher than esophageal temperatures during lower body exercise in the heat which causes a heat sink [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of manual labor work settings, where workers typically endure 8+ hour shifts and must stay safe in the heat, it is preferable to slightly overestimate T C (vs. underestimate) in order to protect these workers from heat-related injuries and illnesses throughout the day. As such, Kenzen’s T C algorithm was designed to slightly overestimate (vs. underestimate) T C at these dangerous T C ranges in order to protect workers, whereas previous algorithms or wearable devices have been shown to underestimate T C at these higher temperatures [ 20 ], which can put workers at even greater risk for heat injury and illness if solely relying on the wearable device for safety feedback. Another point to note is that this slight overestimation of core temperature at T C ≥ 38.5 °C may be even greater when compared to the gold-standard T C measurement of esophageal temperature, since gastrointestinal and rectal temperatures tend to be ~0.24–0.28 °C higher than esophageal temperatures during lower body exercise in the heat which causes a heat sink [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, a core temperature-monitoring algorithm implemented in occupational settings must generally meet the following criteria: (1) small enough not to interfere with the individual’s work tasks, (2) waterproof/sweat proof, (3) continuously (non-invasively) monitor various physiological parameters throughout the day from a single location, (4) be intrinsically safe, and (5) meet the field-established accuracy criteria across a range of body temperatures and environmental conditions [ 9 , 17 ]. While it has been suggested that such T C algorithms could be implemented in a wearable device [ 17 ], we are only aware of one recent study that reported the reliability and validity of a T C algorithm to be implemented in a wearable device using heat flux sensors [ 20 ]. The authors concluded that while this wearable device provided reliable T C measurements, it did not provide accurate T C measurements [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These training sessions were performed with a temperature from 25 to 32°C and with a humidity from 70% to 80%. A specific non-invasive sensor to assess core body temperature (CORE®, green TEG, Switzerland) was used in this training sessions ( Verdel et al, 2021 ). A special focus on hydration was done during this period.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, although such technology might have some limitations in providing an assessment of core body temperature during exercise and its precision should be further evaluated [37][38][39], it might be useful for detecting hyperthermic events in the clinical setting, particularly when compared to other non-invasive methods which might not provide continuous temperature readings [40][41][42] or when patients have to be remotely monitored [1,[43][44][45][46]. Our results showed that a novel non-invasive wireless heat flux-based thermometer was able to detect body temperature changes measured by the tympanic thermometer as the presence or absence of hyperthermia (94.1%) and the presence or absence of fever (97.4%) in the post-stroke clinical setting.…”
Section: Discussionmentioning
confidence: 99%